2018
DOI: 10.5539/jas.v10n7p282
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Section Control Technologies and GPS Auto-guidance Systems Adoption in Cotton Production

Abstract: Using data from a survey of cotton producers in 14 US states, and a bivariate probit regression, this study examined the effects of the following measured parameters on the adoption of Automatic Section Control (ASC) technologies and GPS Auto-Guidance (AG) systems: age, education, farm size, field geometry, information sources, as well as the use of specific production practices and other Precision Agriculture (PA) technologies. Results suggest that younger, more educated producers, consulting farm dealers for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…We postulated that the farmers' age is negatively correlated with farmers' willingness to sell produce through FSMs. As suggested by previous studies, older farmers have shorter planning horizons and, thus, might be less likely to change or modify their production and marketing strategies (Walton et al, 2008;Zhong et al, 2016;Edge et al, 2018;Dong et al, 2019). On the other hand, we hypothesized that education could be positively but also negatively correlated with farmers' willingness to sell produce through FSMs.…”
Section: Variables Hypothesized To Influence Willingness To Sell Prod...mentioning
confidence: 79%
See 1 more Smart Citation
“…We postulated that the farmers' age is negatively correlated with farmers' willingness to sell produce through FSMs. As suggested by previous studies, older farmers have shorter planning horizons and, thus, might be less likely to change or modify their production and marketing strategies (Walton et al, 2008;Zhong et al, 2016;Edge et al, 2018;Dong et al, 2019). On the other hand, we hypothesized that education could be positively but also negatively correlated with farmers' willingness to sell produce through FSMs.…”
Section: Variables Hypothesized To Influence Willingness To Sell Prod...mentioning
confidence: 79%
“…On the other hand, we hypothesized that education could be positively but also negatively correlated with farmers' willingness to sell produce through FSMs. We expect knowledge and information to affect farmer marketing or market outlet choice decisions (Pilgeram, 2011;Zhong et al, 2016;Edge et al, 2018). Those decisions could be to sell but also to not sell produce through FSMs.…”
Section: Variables Hypothesized To Influence Willingness To Sell Prod...mentioning
confidence: 99%
“…Research has shown that when used correctly, common spray technologies, including global positioning system (GPS), rate controller, and section control, can significantly reduce the overapplication of pesticides (Luck et al 2010;Sharda et al 2011Sharda et al , 2013. The benefits from these technologies are further maximized in large and uneven-shaped fields (Edge et al 2018). Today, new application technologies such as pulse-width modulation (PWM) and auto-boom height systems have also been developed and are now available for spray equipment to further improve field and application efficiency.…”
Section: Introductionmentioning
confidence: 99%